THU0174 Analysis of Non-melanoma Skin Cancer Across the Tofacitinib Rheumatoid Arthritis Clinical Programme. (9th June 2015) - Curtis, J.; Lee, E.B.; Martin, G.; Mariette, X.; Terry, K.; Chen, Y.; Geier, J.; Andrews, J.; Kaur, M.; Fan, H.; Nduaka, C.
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). Objectives: The incidence of non-melanoma skin cancer (NMSC) in the tofacitinib RA programme was evaluated using data from randomised Phase (P) 1, 2, 3 and open-label long-term extension (LTE) RA studies (P1P2P3LTE studies). Methods: NMSC data (cut-off date: 30 Aug 2013) were pooled from two P1, eight P2, six P3 and two LTE studies; LTE data collection and analyses are ongoing; study databases unlocked. Patients (pts) with RA in P1, P3 and LTE studies received tofacitinib 5 or 10 mg twice daily (BID) either as monotherapy or with background disease-modifying antirheumatic drugs (DMARDs). LTE pts were enrolled from qualifying P1, P2 and P3 studies; pts from P2 studies received tofacitinib 1 to 30 mg BID or 20 mg once daily. Incidence rates (IRs) per 100 pt-years (py) of exposure for first NMSC were calculated for combined doses (all doses) of tofacitinib in the P1P2P3LTE pt population. The overall NMSC IR was analysed as well as IRs for subgroup analyses according to the following conditions: tofacitinib dose (5 mg vs 10 mg BID); tofacitinib monotherapy vs tofacitinib + background DMARDs; prior tumour necrosis factor inhibitors (TNFi); pt age (≥65 vs <65); ethnic background; and time period. Results: 6092 pts (15103 py of exposure) received tofacitinib (all doses) in the P1P2P3LTE studies. ≥1 events of NMSC occurred in 83 pts receiving tofacitinib (all doses), of which squamous cell carcinomas (SCC) and basal cell carcinomas (BCC) occurred in 39 and 52 pts, respectively. Five pts had a history of NMSC prior to tofacitinib exposure; 78 pts did not. In the P1P2P3LTE population, IRs were 0.55 (95% confidence interval [CI] 0.45, 0.69), 0.26 (0.19, 0.35) and 0.35 (0.26, 0.45) for NMSC overall, SCC and BCC, respectively. NMSC IRs for pts from the P1/2/3 and LTE cohorts receiving tofacitinib 5 mg BID were 0.61 (0.34, 1.10) and 0.41 (0.26, 0.66), respectively; for pts receiving tofacitinib 10 mg BID, NMSC IRs were 0.47 (0.24, 0.90) and 0.79 (0.60, 1.05), respectively. P1P2P3LTE pts on background DMARDs had a numerically higher IR (IR 0.64, 95% CI 0.49, 0.84) than tofacitinib monotherapy pts (IR 0.43, 95% CI 0.30, 0.64). There was a higher rate of NMSC in pts with prior TNFi (IR 1.01, 95% CI 0.67, 1.51) vs TNFi-naïve pts (IR 0.47, 95% CI 0.37, 0.61). Pts ≥65 years had a higher rate of NMSC (IR 1.67, 95% CI 1.19, 2.35) vs pts <65 years (IR 0.38, 95% CI 0.29, 0.51). Pts of White ethnicity had the highest IR of NMSC vs pts of Asian, Black or Other ethnicity (0.86 vs 0.03, 0.00 or 0.14). NMSC IRs, analysed in 6-month intervals (through >84 months), were stable over time. Conclusions: NMSC IRs appeared consistent with published estimates in pts with RA treated with TNFi (IR 0.22-0.66). 1 The overall NMSC IR in the tofacitinib clinical development programme remained stable over time. References: Askling J et al. Pharmacoepidemiol Drug Saf 2011;20:119-130. Acknowledgements: Previously presented (Curtis JR et al. Arthritis Rheum 2014; 66(11): S196 A460) and reproduced with permission. Study sponsored by Pfizer Inc. Editorial support was provided by D Finch, of CMC, and funded by Pfizer Inc. Disclosure of Interest: J. Curtis Grant/research support from: Pfizer Inc, E. B. Lee Consultant for: Pfizer Inc, G. Martin Consultant for: Pfizer, Abbvie, Galderma, X. Mariette Grant/research support from: Pfizer Inc, K. Terry Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Y. Chen Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Geier Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Andrews Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, M. Kaur Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, H. Fan Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Nduaka Shareholder of: Pfizer Inc, Employee of: Pfizer Inc